Inside the mind of the insider - Shaw, Eric D; Post, Jerrold M; Ruby, Keven G (Security Management, 1999)
Companies need to be aware of the possibility of vengeful employees or contractors damaging the company in some way either through fraud or interfering with its computer system - need to carefully screen information technology employees to ascertain whether they possess those characteristics that lends itself to malicious behaviour - characteristics of IT personnel that could cause problems for the company.